Analysis of Eating Behaviors (Picky Eaters), Parents Knowledge of Nutrition and Nutrition Patterns with Nutritional Status of Children Special Needs in SLB Dlanggu Mojokerto District - Miftakhul Muthohiroh; Nurwijayanti Nurwijayanti; Yuly Periostiawati; Sri Kardjati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Children with special needs are required to be able to live independently, adapt and socialize with normal people so that it can escape from the dependence of others. This study aims to study the relationship between nutritional status, nutritional knowledge, and parenting styles of parents with picky eaters in children with special needs in special schools in Mojokerto. The design of this research is analytic observational with a quantitative approach. The population is all students of the Special School in 3 schools in Mojokerto, as many as 186 students. Samples were obtained from some of the SLB students in 3 schools in Mojokerto with a total of 117 respondents. The sampling technique used accidental sampling. The results of this study, most of them experienced the eating behavior of picky eaters in the low category, namely 95 respondents (81.2%), mothers who had sufficient knowledge of nutrition, namely 70 respondents (59.8%), parents who applied parenting styles. dominant instrumental feeding (IF) is 38 respondents (32.5%), respondents with normal nutritional status are 54 respondents (46.2%), picky eater variables and knowledge variables have an effect on nutritional status. Parents must always increase knowledge about how to select, process and serve nutritious food to children, because nutritious food does not have to be expensive and the school must increase its role as a provider of education not only for their children but for parents about nutrition.